The first zoeal stage of Parthenope macrochelos (Herbst, 1790) hatched in the laboratory (Crustacea: Brachyura: Parthenopidae) - Guerao, Guillermo; Abelló, Pere (Scientia Marina, 1999)
The first zoeal stage of the parthenopid crab Parthenope macrochelos is described and illustrated from laboratory-hatched material obtained from an ovigerous crab captured in the western Mediterranean. The first larva of P. macrochelos possesses all the characters as diagnostic of the Parthenopidae and some additional features, including a seta on the basal segment of the endopod of the maxillule and a well developed lateral spine on the telson forks. The present stage is compared with those previously described from other species of the genus Parthenope.